Síntese, caracterização, atividade citotóxica e antimicobacteriana de complexos metálicos com fluoroquinolonas - Oliveira, Leticia Pires de (2018)
This work describes the synthesis and characterization of new platinum complexes of the type [Pt(DMSO)(FQ)Cl]Cl and palladium complexes of the type cis-[Pd(FQ)Cl2], in which FQ represents a fluoroquinolone, namely, levofloxacin, ofloxacin, ciprofloxacin and sparfloxacin. These complexes were characterized by elemental analysis, conductivity and termogravimetric as well as high-resolution mass spectrometric (HRESIMS), IR, UV-Vis and 1H, 13C and 195Pt NMR. The spectral data suggest that the fluoroquinolones act as bidentate ligands coordinated to platinum(II) through the nitrogen atoms of the piperazine ring. The antimycobacterial and anticancer activity of the platinum compounds containing ofloxacin, ciprofloxacin and sparfloxacin were determined. Microbiological assays against wild type Mycobacterium tuberculosis (ATCC 27294) showed that all complexes have been very active, exhibiting antituberculosis activity in low concentrations with MIC values comparable to second line drugs used in the treatment of tuberculosis. The complex with sparfloxacin, [Pt(DMSO)(SPF)Cl]Cl, exhibited the best potential against most drug-resistant Mycobacterium tuberculosis clinical isolates. The cytotoxicity activity of these compounds was also evaluated in three cell lines: MCF-10 (a healthy cell), MCF-7 (a hormone responsive cancer cell) and MDA-MB-231 (triple negative breast cancer cell). The complex [Pt(SPF)(DMSO)Cl]Cl showed IC50 equal 17.3 for MCF-7 cells and 15.3 for MDA-MB-231 cells, with selectivity index 7.8 and 8.8, respectively, being three times more active than cisplatin for MCF-7 line and approximately five times more active than MDA-MB-231 line, being more selective than cisplatin. Flow cytometry analysis revealed that [Pt(DMSO)(SPF)Cl]Cl induced late apoptotic cell death in MDA-MB-231 cells.